Evaporation over Bangladesh - AMIRULHUSSAIN, M (MAUSAM, 1986)
Evaporation observations recorded with Class-A pans at 19 stations in Bangaldesh for a period of five years have been used to present monthly and annual evaporation maps. Highest mean monthly evaporation values of 93.220 mm are recorded ill the northwestern, southeastern and western sides of Bangladesh in April, and of 1142-1636 mm mean annual evaporation values are recorded in northwestern and southeastern parts of Bangladesh, while lowest mean monthly evaporation values of 40-60 mm are recorded in the month of December at the stations Sylhet, Madarlpur & Bhola, and mean annual lowest evaporation value of 700 mm is recorded in Sylhet.